1982
DOI: 10.1111/j.1432-1033.1982.tb06684.x
|View full text |Cite
|
Sign up to set email alerts
|

Anion Binding to Liver Alcohol Dehydrogenase

Abstract: Complex formation at the general anion‐binding site of the liver alcohol dehydrogenase subunit has been characterized by transient‐state kinetic methods, using NADH as a reporter ligand. Equilibrium dissociation constants for anion binding at the site are reported. They conform basically to the lyotropic series of affinity order, with exceptionally tight binding of sulphate. The particular specificity for sulphate might be a general characteristic of anion‐binding enzymic arginyl sites. Anionic species of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…5). The latter rate parameter should be competitively affected by complex formation at the general anion-binding site [9], and data in Fig. 7 confirm that such effects are at hand with a coenzyme-competitive ligand such as SCN-.…”
Section: Binding Site For Cyanidesupporting
confidence: 54%
See 2 more Smart Citations
“…5). The latter rate parameter should be competitively affected by complex formation at the general anion-binding site [9], and data in Fig. 7 confirm that such effects are at hand with a coenzyme-competitive ligand such as SCN-.…”
Section: Binding Site For Cyanidesupporting
confidence: 54%
“…The present investigation was undertaken to obtain such information. Data now reported seem to establish that cyanide (in contrast to a large number of inorganic anions previously examined [9]) combines to catalytic zinc on complex formation with liver alcohol dehydrogenase. We have, therefore, characterized the synergism between coenzyme and cyanide binding to the enzyme by equilibrium measurements and transient-state kinetic methods.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The saturation curve obtained at pH 8.5 could not be satisfactory fitted with eq 5 used earlier (Oldén & Pettersson, 1982). …”
Section: Evaluation Of Rapid Kineticmentioning
confidence: 74%
“…Most earlier studies were performed in phosphate buffers which were shown to be coenzyme-competitive at low pH (Oldén & Pettersson, 1982). In this investigation the presence of any significant concentration of anions, able to interfere with the coenzyme binding process, was strictly avoided.…”
Section: Reasons Why the New Set Of Constants Differs From Earlier Pumentioning
confidence: 99%